Diseño de un programa de gestión técnica de riesgo mecánico, en función de la ISO 13857.2008, para mejorar las condiciones de seguridad industrial y salud ocupacional, del proceso productivo en el área de molinos del grupo Familia. - Velásquez Valdivieso, Jhony Eduardo (2018)
The research project focuses on generating a technical mechanical risk management program, based on ISO 13857: 2008, to improve the industrial safety and occupational health conditions, of the productive process in the area of mills, family group, in this way it will be possible to reduce the mechanical risks that these machines present. When applying guards with safety distances to prevent danger areas from reaching the upper and lower limbs, this project will be fulfilled by identifying the mechanical risks to which the employees are exposed, using the regulations described and defining solutions. By getting to know the origin of the accidents described, conclusions can be generated and corrections made at points of mechanical risks by applying guards to paper machines. The importance of this project is highlighted in the reduction of the accident rate that will be presented in the future when the stated objective is applied, since accidents caused by entrapment will be reduced, generating a positive impact by forming a more reliable and secure work environment, the beneficiaries direct will be the operators that intervene in the production process of the area, and indirect beneficiaries will be all those people who are part of the company.